Development of Company Value Based Digitalization: A Study At State Owned Water Company - Bima Hermastho; Muhammad Ricza Irhamni (Universitas Wahid Hasyim, 2021)
Digitalization management company is a very important condition for increasing competitiveness of company. With the use of digital technology, companies need a change in management process and in the work processes of employee. Researchers have highlighted this as an interesting topic of discussion, and a challenge for companies, including regional water companies. This paper analyzes development of management digitalization in state owned water company. And get the results company value design of state owned water company based digitalization. Keywords: Digitalization, Company Value, Digital Technology and State Owned Water Company.